Model for Development of Solar Energy Potential in Nigeria - J.A. Akinpelu; N.O Adeniji (IJRDO-Journal of Applied Science, 2020)
This study explored the potential of developing solar energy as a viable option in Nigeria. Sunshine-hours data recorded at six synoptic meteorological stations in the country, namely: Sokoto (12.90N, 5.20E), Maiduguri (11.90N, 13.10E), Ilorin (8.40N, 4.50E), Ikeja (6.60N, 3.30E), Port-Harcourt (5.00N, 6.90E) and Enugu (6.50N, 7.60E). over the period 1996-2010 were used. A set of Angstrom constants were obtained and averaged in order to develop the linear regression model for estimation of solar radiation in Nigeria. This model has potential for generating ground observation data of solar radiation at any given location in the country using sunshine hours as the only required input. An Angstrom model of monthly average Clearness Index with normalized sunshine duration was then developed for each of the six meteorological stations. The resulting linear regression model was applied in estimating monthly average daily solar radiation. Regression analysis between computed and measured radiation data was applied to assess the reliability of the generated Angstrom constants. The results generally show a high degree of agreement between the two variables, with correlation coefficients ranging from 0.72 to 0.94. Angstrom constants obtained at the six meteorological stations were thereafter averaged in order to develop a linear regression model for estimating solar radiation in Nigeria. The model developed is for which H is the estimated solar radiation in Nigeria , , the extraterrestrial solar radiation and N is the relative sunshine. Solar radiation values obtained using this model were noted to be in good agreement with those developed for each of the six meteorological stations.